Assessing Turkey's "normative" power in the Middle East and North Africa region: New dynamics and their limitations - (:unkn) unknown (Taylor and Francis Inc., 2016)
In this study, the extent to which Turkey has been pursuing a normative foreign policy (NFP) toward the Arab revolts will be analyzed on the basis of Nathalie Tocci's description of a NFP actor, built on the following three conceptual tools: normative goals, normative means and normative results or impact. With a special emphasis on the conditioning factors that impacted Turkey's pursuit of an NFP, this paper also investigates the limitations and effectiveness of Turkey as an NFP actor in Middle East and North Africa (MENA) in order to understand if Turkey's role in the changing MENA region has gone beyond rhetoric to become empirically justified. It concludes that despite increasing normative representations and rhetoric in its foreign policy, Turkey does not currently possess a cohesive and ambitious NFP agenda and, thus, is still far from being a normative power. © 2015 Taylor & Francis. All rights reserved.